Proceedings of the Conference on Ultrasound in Biology and Medicine – UBIOMED VI - FILIPCZYŃSKI, L. (Archives of Acoustics, 1984)
This publication contains papers and communications which were delivered at the Conference on Ultrasound in Biology and Medicine — UBIOMED VI. This Conference was held in Warsaw–Jabłonna. It was the sixth successive international meeting under this name devoted to these problems. The previous conferences were held in Poland, GDR, Czechoslovakia, Hungary and in USSR. The present conference was held for the second time in Poland. It was organized by the Committee of Acoustics, Polish Academy of Sciences; Ultrasonic Medical and Biological Section, Polish Medical Society; and the Institute of Fundamental Technological Research, Polish Academy of Sciences.